Quantitative assessment of sitting time in ambulant adults with Muscular Dystrophy. - Matthew F Jacques (Public Library of Science (PLoS), 2021)
Background Current investigations into physical behaviour in Muscular Dystrophy (MD) have focussed largely on physical activity (PA). Negative health behaviours such as sedentary behaviour (Physical Behaviour) and sitting time (Posture Classification) are widely recognised to negatively influence health, but by contrast are poorly reported, yet could be easier behaviours to modify. Methods 14 ambulant men with MD and 12 healthy controls (CTRL) subjects completed 7-days of free-living with wrist-worn accelerometry, assessing physical behaviour (SB or PA) and Posture Classification (Sitting or Standing), presented at absolute (minutes) or relative (% Waking Hours). Participant body composition (Fat Mass and Fat Free Mass) were assessed by Bioelectrical Impedance, while functional status was assessed by 10 m walk test and a functional scale (Swinyard Scale). Results Absolute Sedentary Behaviour (2.2 Hours, p = 0.025) and Sitting Time (1.9 Hours, p = 0.030 was greater in adults with MD compared to CTRL and Absolute Physical Activity (3.4 Hours, p < 0.001) and Standing Time (3.2 Hours, p < 0.001) was lower in adults with MD compared to CTRL. Absolute hours of SB was associated with Fat Mass (Kg) (R = 0.643, p < 0.05) in ambulatory adults with MD. Discussion This study has demonstrated increased Sedentary Behaviour (2.2 hours) and Sitting time (1.9 Hours) in adults with MD compared to healthy controls. Extended waking hours in sitting and SB raises concerns with regards to progression of potential cardio-metabolic diseases and co-morbidities in MD.